A single-center, randomized, double-blind, placebo-controlled, crossover investigation of the effects of fexofenadine hydrochloride 180 mg alone and with alcohol, with hydroxyzine hydrochloride 50 mg as a positive internal control, on aspects of cognitive and psychomotor function related to driving a car - Ridout, Fran; Shamsi, Ziba; Meadows, Robert; Johnson, Sigurd; Hindmarch, Ian (Clinical therapeutics, 2003)
Background: Antihistamines (H 1-receptor antagonists) are the mainstay of symptomatic therapy for allergic disorders. Antihistamines are needed that cause no disruptive effects on cognitive and psychomotor function. It is essential that antihistamines maintain the integrity of the cognitive system, not only in ambulatory patients at increased risk of drug-induced traffic- or work-related accidents, but also in students and others whose cognitive or intellectual impairment may adversely affect their performance. Objective; The goal of this study was to investigate the acute effects of fexofenadine hydrochloride 180 mg, alone and with a “social” dose of alcohol, on subjective feelings of sedation and on a battery of objective measures related to driving a car. These measures included information processing, psychomotor speed, and reaction time in an on-the-road car-driving task. Hydroxyzine hydrochloride 50 mg was included in the study as a positive internal control to validate the sensitivity of the psychometri tests to nonspecific impairment. Methods: In this randomized, double-blind, 6-way, crossover study conducted at the Human Psychopharmacology Research Unit, Medical Research Centre (University of Surrey, Guildford, United Kingdom), 18 healthy volunteers received fexofenadine 180 mg, hydroxyzine 50 mg, and placebo alone and with alcohol (0.3 g/kg body weight or ∼0.43–0.50 g/L blood-alcohol concentration). Treatment periods were separated by a washout period of at least 6 days. Subjects performed tests of cognitive and psychomotor performance at 1, 3, and 5 and hours after dosing. The test battery included subjective ratings of sedation, critical flicker fusion (CFF), choice reaction time (including recognition reaction time [RRT], motor reaction time [MRT], total reaction time [TRT], and brake reaction time [BRT]. Results: Eighteen healthy male volunteers (median age, 30.5 years [range, 23–44 years]) were entered into the study. Fexofenadine alone and with alcohol had no significant effect on performance compared with placebo and was not distinguishable from placebo in any of the objective or subjective tests at any point. However, impairment was evident following the administration of hydroxyzine. Hydroxyzine caused significant impairment in CFF ( P < 0.05), RRT ( P < 0.001), and TRT ( P < 0.001) compared with placebo. Hydroxyzine with alcohol significantly disrupted performance on all of the above measures with respect to both placebo and fexofenadine ( P < 0.05) as well as MRT ( P < 0.001). No significant treatment effects on BRT were found. Conclusion: Fexofenadine 180 mg did not have disruptive effects on objective measures related to driving a car and aspects of psychomotor and cognitive function, even when combined with a dose of alcohol equivalent to 0.3 g/kg body weight, in a study in which the psychometric assessments were shown to be sensitive to impairment.